Agile transition and adoption human-related challenges and issues: A Grounded Theory approach - Javdani Gandomani, Taghi; Ziaei Nafchi, Mina (Computers in human behavior, 2016)
Agile methods in software development have been introduced to cope with the inherent problems of the traditional methods. The increasing prevalence of using these methods reflects their important role in the future of software development. However, leaving traditional approach and adapting to Agile approach has been a central attention of the researchers. Indeed, Agile transition needs enough time and effort and most often is subject to several challenges and barriers, mainly because of its people-centric nature. Human-related challenges in several studies have been reported as the major transition challenges. However, exploring the primary origins and reasons of these challenges has received less effort in a large-scale research study. A Grounded Theory in context of Agile software development has been conducted involving 49 Agile practitioners across the 13 different countries. This study identified different aspects of human-related challenges throughout Agile transition process. The results of this study show that the root of the emerged issues is the people's perceptions about Agile transition. The main purpose of this paper is to describe the origins and reasons of these challenges and issues in order to help software companies and development teams. Considering the findings may help them to facilitate Agile transition process with less cost, time and effort and to get better results by considering these potential challenges. •We conducted a large-scale empirical study to study Agile Transition Process (ATP).•Grounded Theory (GT) has been employed as the best choice of research methodology.•Theory of ATP and its various aspects including its challenges have been emerged.•Data analysis led to emerge two main groups of ATP challenges and issues.•The results also revealed the origin and roots of the challenges and issues.